2014
DOI: 10.1038/bjc.2013.817
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of RRM2 by human papillomavirus E7 oncoprotein promotes angiogenesis in cervical cancer

Abstract: Background:The purpose of this study was to confirm that RRM2 as a novel target of HPVE7 involved in cervical cancer angiogenesis.Methods:Gene expression was analysed by RT-qPCR, western blot and immunohistochemistry in cervical cancer tissue and cell lines. Luciferase reporter assay was used to determine the activities of various RRM2 promoters. Secreted VEGF was measured by ELISA. RRM2-mediated capillary tube formation induced by HPVE7 in cervical cancer cells were evaluated using human umbilical vein endoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
82
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(88 citation statements)
references
References 39 publications
6
82
0
Order By: Relevance
“…Previous studies demonstrated that RRM2 protein levels are increased in cervical cancer cells containing integrated viral genomes (Wang et al, 2014). To determine if RRM2 levels are also increased in lines harboring episomal copies of HPV, we compared the level of RRM2 protein in uninfected human foreskin keratinocytes (HFKs) to HPV31 positive CIN162 cells, which are derived from a CIN1 cervical lesion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated that RRM2 protein levels are increased in cervical cancer cells containing integrated viral genomes (Wang et al, 2014). To determine if RRM2 levels are also increased in lines harboring episomal copies of HPV, we compared the level of RRM2 protein in uninfected human foreskin keratinocytes (HFKs) to HPV31 positive CIN162 cells, which are derived from a CIN1 cervical lesion.…”
Section: Resultsmentioning
confidence: 99%
“…RNR activity is important to genomic integrity, as well as cell viability, with an increase or imbalance of dNTP pools leading to mutagenesis (Hu and Chang, 2007), and decreased dNTP levels leading to impaired DNA replication and repair (Nordlund and Reichard, 2006). Previous studies demonstrated that RRM2 transcript and protein levels are increased in cervical cancer lines containing chromosomally integrated HPV16 and HPV18 genomes (Wang et al, 2014). HPV16 E7 was found to be sufficient to increase RRM2 transcript levels, however, whether RRM2 is increased in lines containing episomal HPV genomes and is important for viral replication has not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…Although only three patients were assigned to the PR molecular subtype, the hazard for TTT was 9-fold the average, identifying a subset of patients with imminent progression, as also reported by Hose et al 32 The top gene in the GEP4 model, RRM2, is the beta subunit of ribonucleotide reductase (RNR). RRM2 overexpression is associated with cellular invasiveness, metastasis and tumor angiogenesis 33 via activation of the ERK1/2 signaling pathway 34 in cancer. RRM2 expression independently identified 15.2% patients with a 2-year TTT estimate of 75% (Online Supplementary Figure S1).…”
Section: Discussionmentioning
confidence: 99%
“…The quantitative RT-PCR (qRT-PCR) data were analyzed using the method of 2 j$$Ct relative expression quantity as previously described. 21 All the qRT-PCR reactions were run in triplicate.…”
Section: Rna Isolation and Quantitative Real-time Pcrmentioning
confidence: 99%